Implementation of Students Character in the Batik Them P5 Project at Elementary School - Silvi Jihan Mahfiroh; Nur Aviatul Faizah; Farah Alifanty Rahmania; Nadhilah Aisyah Amalia; Mohammad Faizal Amir (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Character is an identity for each individual that is formed from behavior and frame of mind. An important component that must be present in students is character education. The school must consistently educate students' character so that students can get used to the school culture implemented through the P5 program. This study aims to determine the value of student character education in the batik theme P5 project with character development in line with the Pancasila Student Profile. This research uses a qualitative descriptive method to determine the facts and describe the object under study. Data were collected through observation and interviews. The result of this study is the character of Muhammadiyah 9 Ngaban Elementary School students in the P5 batik project, which refers to the dimensions of the Pancasila learner profile, including faith, devotion to God Almighty, and noble character, independence, mutual cooperation, global diversity, critical reasoning, and creativity.